Calculation, Life and Temporality: on Some Elements of Consonance Between Cryptoeconomy and Techno-Manipulation of Nature - Doria, Luigi (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
The debate on the cryptoeconomy develops in various fields, from those related to the question on the economic meaning of some controversial projects to those regarding the interpretation of the socio-political frameworks of the blockchain revolution. Part of the debate addressed, in particular, the implications of innovation paths in ecological terms, with regard, for example, to the potential of new objects such as environmental tokens or to the environmental impacts of certain cryptocurrencies. This article looks at the relationship between cryptoeconomic innovation and environmental dynamics from a peculiar perspective. In fact, the article moves from the identification, at the heart of some areas of the cryptoeconomy, of a movement of cybernetization of the economy that has profound implications on the conceptions of economic life and its temporality. On the one hand, the cryptoeconomy is the locus of a continuous production of artificial certainties and of a cybernetic “assurance” of socio-economic phenomena. On the other hand, at the heart of some cryptoeconomic ideological apparatuses we find a project aimed at transcending the reference to the human as the main actor in economic life, within a conceptual framework characterized by the unconditional and unlimited hybridization between human and machinic. Now, these tendencies manifest certain consonances with what happens in the world of the techno-manipulation of nature. The treatment of natural reality proceeds under the banner of ever new forms of enhancement and transformation, which are in turn intimately connected to processes of capitalist valorization. Moreover, as pointed out by an important line of sociological thought, the exploitation of nature needs to be understood by considering contemporary ontological politics, and thus the movement within which some ontological boundaries are questioned: the boundary between the natural and the technical, but also the ones between the living and the non-living and between the human and the non-human. The task for scholarly reflection - I argue in the article – is to interpret the consonances between the two macro-areas. One of the privileged terrains for this task concerns the reflection on what contemporary techno-capitalism - in all its configurations, including the crypto-economic and environmental ones and in its ontological torsion – seemingly aims to definitively deny, i. e. the dimension of limit.